Potensi Penghambatan Enzim Αlfa-Glukosidase dan Tes Toleransi Glukosa Oral (TTGO) Ektrak Daun Dadap Serep (Erythrina subumbrans (Hassk) Merr.): - Susilawati, Elis; Astuti, Ayu Dwi; Sulaeman, Agus (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2023)
Abstract: Spare dadap plants contain flavonoids that can potentially lower glucose levels in the blood and reduce glucose absorption in the intestine. The purpose of the study was to determine the inhibitory activity of the α-glucosidase enzyme and the effect of giving Spare Dadap Leaf Ethanol Extract (EEDDS) on blood glucose levels of male white Wistar rats and its effective dose. The research method used the in vitro method with inhibition of α-glucosidase enzyme and the in vivo method Glucose Tolerance Test (TTGO) with amylum manihot induction using 25 rats divided into 5 groups with EEDDS doses of 100, 200, and 400 mg / kg BB, then measured blood glucose levels for 120 minutes. The results of the EEDDS α-glucosidase enzyme inhibition study showed the best % inhibition value of 41.81% at 100 ppm and the lowest % inhibition value at 10 ppm, which was 13.33% with an IC50 value of 146.30 ppm, which was included in the weak category in inhibiting α-glucosidase. The results of TTGO research induced amylum manihot, EEDDS 400 mg / KgBW have a significant effect on reducing blood glucose levels in the T60 to T120 range. The conclusion in this study is that spare dadap leaf ethanol extract has potential as an antihyperglycemic both in vitro and in vivo.